EXPERIENCE REPORT ON THE CONSTRUCTION OF A MEDICAL RECORD FOR INTEGRATIVE AND COMPLEMENTARY HEALTH PRACTICES AT CEPIC/UFT - Clara dos Santos Rodrigues, Ana; Carolina Moreno, Ana; Edith Farias Lima, Ana (Health and Society, 2025)
This experience report describes the development of a specific medical record for Integrative and Complementary Health Practices at the Center for Integrative and Complementary Health Practices of the Federal University of Tocantins. The initiative aimed to develop a digital tool that enables systematic patient registration and integrated monitoring, considering the uniqueness and comprehensiveness of the care offered by the PICS. The methodology adopted was participatory, involving the collaboration of health professionals, researchers, and users of this Center, ensuring the practical and theoretical adequacy of the medical record. As a result, a digital medical record was structured containing essential information for monitoring integrative therapies, contributing to the safety, quality, and continuity of care. The experience highlights the feasibility and importance of implementing specific instruments for integrative care, which can serve as a reference for other institutions working in the field.